2005
DOI: 10.1002/tox.20129
|View full text |Cite
|
Sign up to set email alerts
|

Diesel exhaust affects immunological action in the placentas of mice

Abstract: We investigated the effect of diesel exhaust (DE) on pregnancy and fetal development in mice at day 14 postcoitum (pc) with a special focus on the placenta. The number of absorbed fetuses increased in groups exposed to DE, and congestion was observed in histological sections of placentas. During placental absorption expression of CYP1A1 mRNA decreased to undetectable levels, whereas expression of TNF alpha mRNA increased approximately twofold over that of the control. Levels of CYP1A1 mRNA in normal placentas … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
2
4

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 55 publications
(33 citation statements)
references
References 44 publications
1
26
2
4
Order By: Relevance
“…Control: n = 8, TiO 2 : n = 8. Presented are the mean ± S.E., where * , p < 0.05, * * , p < 0.01, * * * , p < 0.001. have observed various histologic and functional effects on the male reproductive and central nervous systems in mice exposed prenatally to diesel exhaust (DE) [13][14][15][16][17][18] and diesel exhaust particles (DEP). The changes in the reproductive and central nervous systems in DE-exposed mice could be reduced by eliminating particles including nano-sized particles with a high-quality filter (unpublished data).…”
Section: Discussionmentioning
confidence: 99%
“…Control: n = 8, TiO 2 : n = 8. Presented are the mean ± S.E., where * , p < 0.05, * * , p < 0.01, * * * , p < 0.001. have observed various histologic and functional effects on the male reproductive and central nervous systems in mice exposed prenatally to diesel exhaust (DE) [13][14][15][16][17][18] and diesel exhaust particles (DEP). The changes in the reproductive and central nervous systems in DE-exposed mice could be reduced by eliminating particles including nano-sized particles with a high-quality filter (unpublished data).…”
Section: Discussionmentioning
confidence: 99%
“…6465); Fax: +81-4-7121-3784; E-mail: j3108703@ed.noda.tus.ac.jp monoxide, sulfur oxides, nitrogen oxides, and DE particles (DEPs). Numerous studies have indicated that DE and DEPs have various detrimental effects on health; it has been reported that DE in humans causes lung cancer, 1) chronic obstructive pulmonary disease, 2) cardiovascular disease, [3][4][5][6] and in mice, reduced male reproductive function, [7][8][9][10] abnormal fetal development of female reproductive function, 11) abnormal expression of immune-related genes in the placenta, 12) and central nervous system damage. 13) It has also been reported that DE exposure promotes allergic reactions in the airway and exaggerates the pathology of respiratory allergic diseases.…”
Section: Introductionmentioning
confidence: 99%
“…Une expérience similaire chez la souris avec des nanoparticules de cadmium induit aussi des perturbations de la stéroïdogenèse ; bien que la taille foetale soit aussi réduite, le poids des foetus n›est pas affecté, mais celui des placentas à terme est augmenté (Blum et al 2012). Chez la souris, une exposition similaire pendant la plus grande partie de la gestation induit des résorptions embryonnaires et foetales accompagnées de lésions placentaires importantes (hémorragies, congestion, nécrose, compaction des espaces vasculaires, infiltration de cellules immunitaires et stress oxydatif) (Fujimoto et al 2005 ;Weldy et al 2014). Aux concentrations d'exposition les plus élevées, l'expression génique placentaire de plusieurs cytokines proinflammatoires (interleukines IL-4, IL-5, IL-6, IL-12a et b) est très largement augmentée (Fujimoto et al 2005).…”
Section: Exposition Par Inhalationunclassified
“…Chez la souris, une exposition similaire pendant la plus grande partie de la gestation induit des résorptions embryonnaires et foetales accompagnées de lésions placentaires importantes (hémorragies, congestion, nécrose, compaction des espaces vasculaires, infiltration de cellules immunitaires et stress oxydatif) (Fujimoto et al 2005 ;Weldy et al 2014). Aux concentrations d'exposition les plus élevées, l'expression génique placentaire de plusieurs cytokines proinflammatoires (interleukines IL-4, IL-5, IL-6, IL-12a et b) est très largement augmentée (Fujimoto et al 2005). L'exposition in utero à des concentrations élevées de DE induit aussi une augmentation marquée de l'expression d'interleukines (IL-1b, IL-6, IL-10) et de chimiokines (chemokine ligand 2 et fractalkine) dans le cerveau des foetus à terme (Bolton et al 2012 (Valentino et al 2016).…”
Section: Exposition Par Inhalationunclassified